Automating pandemic mitigation. (3rd May 2021) - Magid, Evgeni; Zakiev, Aufar; Tsoy, Tatyana; Lavrenov, Roman; Rizvanov, Albert
Abstract : The COVID-19 pandemic keeps spreading across the world and, while national governments concentrate on lockdowns and restrictions to mitigate the disaster, advanced technologies could be employed more widely to fight the pandemic. This paper surveys existing robotic solutions that could be employed for pandemic care and presents a systematized description of desired robot properties based on a particular application area and target users. We propose a new generation infection hospital framework that integrates existing robotic tools toward pandemic mitigation and discuss ethical aspects of their use within the framework. GRAPHICAL ABSTRACT: